Higher Quality Exhaustible Resource Deposits Receiving Higher or Lower Resource Rents in a Simple Spatial Framework - John Hartwick (Queen's University, Department of Economics, 2013)
Kolstad's (1994) model of intertemporal, competitive supply to a linear market from two distinct exhaustible resource deposits admits two different interior solutions - one with the low cost deposit 'earning' the higher resource rent and the other with the low cost deposit 'earning' the lower resource rent. This latter outcome turns on the initial size of the low cost deposit being signi.cantly larger than the high cost deposit. We infer then that size can trump quality in the determination of the resource rent for a deposit, when geography is explicit.
Keywords: D49; Q31; D21; 330; exhaustible resource extraction; deposit quality; linear market